Angiotensin-Converting Enzyme 2 Activity Is Associated With Embolic Stroke of Undetermined Source. Issue 7 (11th June 2021) - Sajeev, Jithin K.; Dewey, Helen; Kalman, Jonathan M.; Chou, Bon; Roberts, Louise; Cooke, Jennifer C.; Koshy, Anoop N.; Patel, Sheila K.; Gould, Merryn; Ngoh, Jeremy; Burrell, Louise M.; Teh, Andrew W.
Abstract : Supplemental Digital Content is available in the text.